CHILD-FRIENDLY MADRASAS WITH HUMANISTIC-BASED EDUCATION - Segaf Baharun (Jurnal Pendidikan Islam, 2022)
The teaching and learning process at child-friendly madrasas ensures that children's rights are fulfilled. A democratic learning environment based on children's rights, where the learning process is also tailored to the child's abilities and interests. In addition, child-friendly madrasas offer the learners freedom. Since all rules created by educational institutions require student participation, this context refers to the freedom of students to articulate their thoughts and realize their full potential. This study attempts to characterize child-friendly madrasas in the context of freedom of learning. This study uses a library-based research methodology that utilizes books and scholarly articles on the subject of child-friendly madrasas. In order to create child-friendly schools, educational institutions must ensure that the teaching and learning process takes place in a safe and pleasant environment. In terms of gender sensitivity, there is no gender discrimination. Added to this are democratic participation and a healthy, safe and secure environment.